2017
DOI: 10.1016/j.pbb.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Predator odor exposure of rat pups has opposite effects on play by juvenile males and females

Abstract: Juvenile social play behavior is one of the earliest sexually differentiated behaviors to emerge. In rats, as with most other species that play, males engage in more rough-and-tumble play compared to females. Exposure to early life adversity is a major driver of adult health and can manifest differently in males and females. However, the effects of adverse early life exposure on play behavior in the juvenile period are poorly understood. To address this, male and female neonatal rats were exposed to predator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 101 publications
1
13
1
Order By: Relevance
“…We were surprised to find a lack of sex differences among Sprague‐Dawley subjects in either test, as almost all published studies have documented sex differences in this strain (Argue & McCarthy, ; Argue et al, ; Casto et al, ; Edelmann et al, ; Hotchkiss et al, ; Jessen et al, ; Krebs‐Kraft et al, ; Kurian et al, ; Olesen et al, ; Olioff & Stewart, ; Stockman & McCarthy, ; Wood et al, ), with the exception of Himmler et al () and those that found female‐biased sex differences (Field et al, ; Madden & Zup, ; Mychasiuk et al, ; Wood et al, ). However, the context in which our rats played differed in at least one way from that used in any of these previous studies.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…We were surprised to find a lack of sex differences among Sprague‐Dawley subjects in either test, as almost all published studies have documented sex differences in this strain (Argue & McCarthy, ; Argue et al, ; Casto et al, ; Edelmann et al, ; Hotchkiss et al, ; Jessen et al, ; Krebs‐Kraft et al, ; Kurian et al, ; Olesen et al, ; Olioff & Stewart, ; Stockman & McCarthy, ; Wood et al, ), with the exception of Himmler et al () and those that found female‐biased sex differences (Field et al, ; Madden & Zup, ; Mychasiuk et al, ; Wood et al, ). However, the context in which our rats played differed in at least one way from that used in any of these previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…However, the context in which our rats played differed in at least one way from that used in any of these previous studies. Many tested play in larger groups (Argue et al, ; Casto et al, ; Edelmann et al, ; Jessen et al, ; Krebs‐Kraft et al, ; Kurian et al, ; Olesen et al, ), some tested subjects in a novel environment (Argue & McCarthy, ; Argue et al, ; Krebs‐Kraft et al, ; Olioff & Stewart, ; Stockman & McCarthy, ; Wood et al, ), and others isolated subjects prior to testing (Hotchkiss et al, ; Wood et al, ). Therefore, Sprague‐Dawley males may be particularly sensitive to those environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations